HUBUNGAN DUKUNGAN SOSIAL DENGAN PSYCHOLOGICAL ADJUSTMENT PADA IBU RUMAH TANGGA - -, Raudatussalamah; Alsurra, Siti (Persepsi: Jurnal Riset Mahasiswa Psikologi, 2024)
Housewives are vulnerable to experiencing emotional disturbances, even severe depression, due to the lack of assistance to alleviate their difficulties or changes in their lives. One of the significant factors related to psychological adjustment is social support. This study aims to determine the relationship between social support and psychological adjustment in housewives. The research design is correlational, using non-probability sampling techniques, and data analysis using Pearson correlation test. The study subjects consisted of 100 housewives in Kampung Tengah, Sukajadi District, Pekanbaru City. Research data were obtained using the Social Provisions Scale to measure social support (α = 0.931) and the Psychological Adjustment scale to measure Psychological Adjustment (α = 0.831). The analysis technique used was the Pearson product-moment. The results showed that there was a significant correlation between social support and psychological adjustment with a significance value of P = 0.000 (p <0.05) with a contribution value of 59.2%. This means that housewives can make psychological adjustments, and the level of social support received by them is high. This study found a positive relationship between social support and psychological adjustment with a correlation coefficient of 59.2%. Keywords: Social Support, Psychological Adjustment, Housewives